ANALISIA HIDROGRAF SATUAN DAN WIND ROSE PLOTS PADA DAERAH ALIRAN SUNGAI SEKANAK - Destania, Henggar Risa; Syarifudin, Achmad (Jurnal Tekno, 2020)
Sekanak watershed is a basin in Palembang which is often affected by flood during the rainy season. The characteristics of the watershed by the impact of changes in land-use by economic and settlement developments. Sekanak watershed has 3 retention ponds which have the function of accommodating temporary discharge during floods. The catchment capacity of the watershed soil type, storage conditions etc. Therefore we need an analysis of the transformation of rainfall data in the watershed into a flow at the watershed control point and an analysis of the transformation of runoff volume (effective rain) into a surface runoff hydrograph (unit hydrograph). Hydrographs measured at a watershed control point are the response or output from rain that falls on a watershed system. The size of the watershed depend on the watershed system. This is closely related in analyzing the availability of water that occurs in the watershed system.